Speaking, thinking, seeing: three verbs of Balzac’s gastronomy - Frattini, Paula Caldas (Revista Criação & Crítica, 2017)
The present article intends to discuss how Balzac’s poetics ascribes an essential status to food in the representation of the nineteenth century man’s life in The Human Comedy. From a panoramic reading of Balzac’s novels, we firstly aim to analyse the relationship between the commensality and the formal characteristics of the text. Secondly, pursuing another direction of his poetics, we highlight the epistemological dimension in the movement of Balzac’s thought present in the narrative. Finally, as it could not be otherwise, considering Balzac’s poetics, we review the relationship between the descriptive and the visual aspects of the gastronomic representation.